Supplier selection in government organizations based on fuzzy evaluation approach / Fairuz Shohaimay, Nazirah Ramli and Siti Rosiah Mohamed - Shohaimay, Fairuz; Ramli, Nazirah; Mohamed, Siti Rosiah (Research Management Institute (RMI), 2012)
Asset purchasing is one of the main responsibilities of Information Technology (IT) department which involves selecting the best supplier. The IT department needs to consider many criteria such that the chosen supplier offers the best product and services at acceptable price, without compromising on the quality and standards of goods. Thus, supplier selection is a multi-criteria decision making (MCDM) problem. In real practice, supplier selection is a complex decision making task. The evaluation process of suppliers relies heavily on previous experiences and human judgments which are vague and uncertain. It is relatively difficult for decision makers to provide exact numerical values for the criteria. Hence, fuzzy set theory was introduced to deal with uncertainties and imprecision in linguistic terms values in decision making processes. Although linguistic terms are used in many fuzzy MCDM models, most of the corresponding fuzzy numbers were fixed and taken from the previous literatures. These fuzzy numbers may not necessarily reflect actual respondents' opinions. Therefore, a two-phased fuzzy evaluation technique is proposed in evaluating and selecting suppliers. Firstly, triangular fuzzy numbers were built based on respondents' opinions. Fuzzy evaluation method is used to evaluate the suppliers based on three main criteria and nine sub-criteria. Finally, the suppliers were ranked using distance minimization method…